Toward a clinical antifungal peptoid: Investigations into the therapeutic potential of AEC5. Issue 6 (2nd April 2019) - Spicer, Sabrina K.; Subramani, Aarthi; Aguila, Angelica L.; Green, R. Madison; McClelland, Erin E.; Bicker, Kevin L.
Abstract: Cryptococcus neoformans is a fungal pathogen that causes cryptococcal meningitis in immunocompromised individuals. Existing antifungal treatment plans have high mammalian toxicity and increasing drug resistance, demonstrating the dire need for new, nontoxic therapeutics. Antimicrobial peptoids are one alternative to combat this issue. Our lab has recently identified a tripeptoid, AEC5, with promising efficacy and selectivity against C. neoformans . Here, we report studies into the broad‐spectrum efficacy, killing kinetics, mechanism of action, in vivo half‐life, and subchronic toxicity of this compound. Most notably, these studies have demonstrated that AEC5 rapidly reduces fungal burden, killing all viable fungi within 3 hours. Additionally, AEC5 has an in vivo half‐life of 20+ hours and no observable in vivo toxicity following 28 days of daily injections. This research represents an important step in the characterization of AEC5 as a practical treatment option against C. neoformans infections. Abstract :